2019
DOI: 10.1007/s11187-019-00267-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, innovation and entrepreneurship: where are we and where should we go in future studies?

Abstract: In this paper, we review and comment upon the development of the literature on diversity, innovation, and entrepreneurship. In an overview of previous studies and various strands of literatures, we outline and argue that to better understand the intricate dynamic relationships between diversity, innovation, entrepreneurship, and regional development there is a strong need to further develop "the economics of spatial diversity." We further argue that this development may benefit from combining various literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 113 publications
1
24
0
4
Order By: Relevance
“…Our analysis highlights the elements of entrepreneurial ecosystems associated with each developmental stage of diverse initiatives in developed and developing countries. Our results contribute to the academic discussion about the definitions/measures of entrepreneurship (Iversen et al 2007;Henrekson and Sanandaji 2019), entrepreneurial process (Busenitz et al 2014), entrepreneurial ecosystems (Acs et al 2017;Audretsch 2019), diversity of entrepreneurship (Welter et al 2017;Karlsson et al 2019), and economic development (Urbano et al 2019). A research agenda is proposed for the analysis of those gaps identified across the entrepreneurial processes and types of economy.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Our analysis highlights the elements of entrepreneurial ecosystems associated with each developmental stage of diverse initiatives in developed and developing countries. Our results contribute to the academic discussion about the definitions/measures of entrepreneurship (Iversen et al 2007;Henrekson and Sanandaji 2019), entrepreneurial process (Busenitz et al 2014), entrepreneurial ecosystems (Acs et al 2017;Audretsch 2019), diversity of entrepreneurship (Welter et al 2017;Karlsson et al 2019), and economic development (Urbano et al 2019). A research agenda is proposed for the analysis of those gaps identified across the entrepreneurial processes and types of economy.…”
Section: Introductionmentioning
confidence: 76%
“…Our paper contributes towards academic debates in the field: (a) the debate regarding the entrepreneurial process (Busenitz et al 2014) and operational definitions of entrepreneurship (Iversen et al 2007;Henrekson and Sanandaji 2019); (b) the discussion about which elements of entrepreneurial ecosystems are of significance per type of entrepreneurship (Acs et al 2017;Audretsch 2019); (c) the analysis of the relationship between the diversity of entrepreneurship and context (Welter 2011;Welter et al 2017;Karlsson et al 2019); and (d) the relationship between entrepreneurship, environmental conditions, and economic development (Urbano et al 2019). We hope that our study also inspires researchers to extend the analysis of the reasons why diversity is so crucial for entrepreneurship and societal development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jacobs (1969) discusses the urbanization process to be one of the most important growthenhancing phenomena. In comparison with less dense areas, urban areas have an advantage in having greater access to diversity both in terms of individuals and industries/firms (Glaeser 2011;Karlsson et al 2019). Transport costs are lower in cities (Glaeser et al 2001); technology is better; ideas and knowledge travel faster across individuals and firms (Jacobs 1969); and labor market matching is more efficient (Marshall 1890)-all inducing productivity in cities (Duranton and Puga 2004).…”
Section: Geography Of Voting Behavior and Regional Developmentmentioning
confidence: 99%